Walking through the jungle - Lacome, Julie (Cambridge, MA Candlewick Press, 1993)
In this traditional English nursery rhyme, a young boy imagines the sounds made by various animals in the jungle.
"Published in Great Britain in 1993 by Walker Books Ltd., London."--Page facing t.p.
School Library Journal
Publisher's Weekly
Booklist
1.5
K-3
Keywords: Nursery rhymes, English; Children's poetry, English; Nursery rhymes; Jungle animals -- Poetry; Animal sounds -- Poetry; Nursery rhymes; Jungle animals -- Poetry